Agricultural Extension: Global Status and Performance in Selected Countries: Synthesis of Conclusions - Babu, Suresh Chandra (2020)
Suresh Babu BOOK LAUNCH Virtual Event - Agricultural Extension: Global Status and Performance in Selected Countries Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) SEP 10, 2020 - 09:30 AM TO 11:00 AM EDT